A cross-sectional comparison of breastfeeding knowledge, attitudes, and perceived partners' support among expectant couples in Mekelle, Ethiopia - Kidane Tadesse Gebremariam; Oksana Zelenko; Afework Mulugeta; Danielle Gallegos (BMC, 2021)
Abstract Background Breastfeeding is considered the biological norm and essential to reduce infant morbidity and mortality. Mothers are responsible for breastfeeding but the support of others, including their partners is an influential determinant. The aim of this study was to compare antenatal breastfeeding knowledge, attitudes, and perceived breastfeeding support of expectant couples in Mekelle, Ethiopia. Methods As part of a randomised controlled trial of an mHealth intervention, 128 couples in their third trimester from three selected health centres in Mekelle city were recruited to participate between September and October 2018. Couples who each had a personal mobile phone, read and spoke Tigrigna, and lived together were included. Baseline data on breastfeeding knowledge, attitudes, and perceived support (breastfeeding savvy, help, appreciation, presence and responsiveness) were collected using previously validated tools through interview by health workers. Results Compared to mothers, male partners were more likely to indicate their intention to provide breastfeeding appreciation (p = 0.02), breastfeeding presence (p = 0.002), and breastfeeding responsiveness (p = 0.04). The mothers' prenatal perception of their partners' intended breastfeeding support was lower than fathers' perceptions to support their partners. Multiparous mothers had more positive perceptions regarding their partners' breastfeeding savvy (p = 0.03), and breastfeeding help (p = 0.02) compared to primiparous mothers. Conclusions Fathers in Ethiopia are potentially strong supporters of breastfeeding practice. Future breastfeeding interventions should promote the involvement of fathers in breastfeeding and encourage mothers to increase their partners' involvement in breastfeeding.